Elementary Course in Woodwork : Designed for use in high and technical schools, with one hundred and thirty-four illustrations: First Edition - Ross, George Alexander (Salt Lake City, UT : Project Gutenberg, 2021)
"Elementary Course in Woodwork" by George Alexander Ross is a technical manual written in the early 20th century. The book is designed to serve as a guide for students studying elementary woodwork in high and technical schools, specifically tailored for those at the Lewis Institute in Chicago. It addresses essential woodworking skills, covering various techniques and tools used in carpentry, joinery, and pattern making. The opening of the manual sets the stage for a structured learning path, outlining the course's objectives and timeline. Ross emphasizes a systematic approach to woodworking, gradually moving from simpler to more complex operations. The preface details the practical exercises included in the course, the necessary tools and equipment, and the foundational knowledge students must acquire to succeed. The text features detailed information about the care and use of saws, alongside rules for safe and efficient woodworking practices, thereby equipping students with the essential skills for their future endeavors in this craft. (This is an automatically generated summary.)
Release date is 2021-10-26
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Woodwork (Manual training)